Development, validity, and test-retest reliability of a new neurocognitive functional performance test: The choice-reaction hop test. (January 2023) - Rosen, Adam B.; Choi, Ji Yeon; Anderson, Katie; Remski, Lindsey E.; Knarr, Brian A.
Abstract: Objectives: To validate a choice-reaction hop test (CRHT) by assessing differences in timing versus the side-hop test (SHT), and to determine the CRHT's test-retest reliability. Design: Test-retest reliability. Setting: Laboratory. Participants: Forty-nine healthy adults participated (16 female; age = 22.7 ± 3.4 years; height = 174.9 ± 9.1 cm; mass = 75.4 ± 14.8 kg). Main outcome measures: Participants completed three trials each of the SHT and the CRHT in a counterbalanced order. Participants returned one-week later to repeat the CRHT. The fastest and the mean of the three trials were compared. Results: Participants took significantly longer to complete the CRHT (Mean across 3 trials = 21.4 ± 3.4s, Fastest trial = 19.7 ± 3.0s) compared to the traditional SHT (10.4 ± 2.0s, p < 0.001). The CRHT demonstrated good-excellent test-retest reliability across testing days for both the mean across 3 trials (r = 0.890, p < 0.001, SEM = 1.13) and the fastest trial (r = 0.828, p < 0.001, SEM = 1.24). Conclusion: Compared to the SHT, the CRHT took longer to complete indicating its ability to stress neurocognitive function during an FPT. The CRHT demonstrated good-excellent test-retest reliability, which may allow it to be a useful measure in serial evaluations such as during rehabilitation benchmarking. The CRHT may be an effective FPT to assess combined physical and neurocognitive function to assist clinicians in evidence-based decision-making. Highlights: The choice-reaction hop test assesses combined physical and neurocognitive function. The choice-reaction hop test demonstrated good-excellent test-retest reliability. The choice-reaction hop test may be useful for return-to-sport decision-making.